The Metaphysics of Emergence - Campbell, R. author. aut Link
X, 333 p.
Keywords: This book argues that a plausible account of emergence requires replacing the traditional assumption that what primarily exists are particular entities with generic processes. Traversing contemporary physics and issues of identity over time, it then proceeds to develop a metaphysical taxonomy of emergent entities and of the character of human life.